Manajemen Usaha Kesehatan Sekolah Dalam Mendukung Peningkatan Mutu Pendidikan Di SLB Negeri Pembina Yogyakarta - Ratesih, Asih; Rejokirono, Rejokirono (Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to determine the current management of the School Health Unit in Special Schools in an effort to support the improvement of the quality of education, especially in Pembina State Special Special Schools in Yogyakarta. This research uses a qualitative approach with descriptive qualitative type. The subjects of this study were school principals and teachers at the Pembina State Special School in Yogyakarta. Data collection techniques using observation, interviews, and documentation. To perform data analysis using the Miles and Huberman model with the steps of data collection, data condensation, data presentation, and drawing conclusions. Checking the validity of the data is by increasing persistence and using triangulation of sources and data collection techniques. The results of this study indicate that the management of the School Health Efforts at the Pembina State Special School in Yogyakarta has been going well starting from planning, organizing, directing, and controlling. Management of School Health Businesses at the Pembina State Special Special School in Yogyakarta has a direct and indirect positive impact on improving the quality of education at the Pembina Yogyakarta Special Special School